Family cohesion, children’s thoughts, and children’s cognitive assessments: Mediating role of sport anxiety - Юмна Али; Сайед М. И. Шах (Психология человека в образовании)
Introduction. The aim of this quantitative cross-sectional correlational study is to explore the relationship between family cohesion and children’s cognitive assessments. Today, against the backdrop of digitalization, it is crucial to emphasize the importance of sports to ensure people have more physical activity. From the perspectives of sports psychology and education, understanding the role of parental involvement, family bonding, and boundaries is essential for exploring their impact on children’s sports performance.